Avaliação do sono de crianças : análise retrospectiva em um centro de referência norte-americano - Marinho, Beatriz Araujo Lage (2013)
Introduction: Obstructive Sleep Apnea Syndrome (OSAS) in children, as defined by the American Thoracic Society, is a disorder of breathing during sleep characterized by prolonged partial airway obstruction and/or intermittent complete obstruction (obstructive apnea) that disrupts normal ventilation during sleep and normal sleep patterns. Objective: This study aimed to investigate retrospectively the prevalence of OSAS among children aged 6 to 12 years old, evaluated through polysomnography and sleep questionnaires between 2011 and 2012, analyzing severity, symptoms and associated risk factors. Methods: We evaluated 63 children referred to the Sleep Laboratory of the Dell Children’s Hospital in Austin, Texas (USA) with suspition of Sleep Disordered Breathing. The patients were submitted to a pre-sleep questionnaire and to polysomnography. Results: The mean age was 8,8 ±1,9 years old, and 55,6% of the children were male. Children without OSAS accounted for 30,2% of the sample. The OSAS observed in the remainder was mild in 49,2%, moderate in 11,1% and severe in 9,5%. Gender and age were not associated with OSAS. Hispanic and African-American children were at higher risk for OSAS. Twenty two hispanic children presented OSAS ( 88%) and ten African-american children presented OSAS (83,3%). In children with OSAS, the most common symptoms were: snoring (86%), periodic limb movements (64,3%), arousals during sleep (60,5%) and restless sleep (58,1%). Excessive daytime sleepiness was reported in only 33,3% of the patients. Bruxism was more prevalent among the patients without OSAS (52,6%) than in the patients with OSAS (31%). Overweight children were at higher risk for OSAS. Conclusions: Overweight children are at a higher risk for developing OSAS. Hispanic and African American children presented a higher risk for developing OSAS. Age and gender were not associated to the diagnose of OSAS. Bruxism was more prevalent among the children who did not present OSAS.